John Marston’s "Poules-worke": Smellscapes and Scent Effects in Antonio and Mellida, Antonio’s Revenge, Jack Drum’s Entertainment, and What You Will - Preedy, Chloe Kathleen (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2026)
Olfactory effects in John Marston’s late Elizabethan plays for the Children of Paul’s – Antonio and Mellida, Antonio’s Revenge, Jack Drum’s Entertainment, and What You Will – demonstrate how his children’s company drama works with its specific production site. By including tobacco, perfume, torch fumes, and incense, odours familiar to residents of and visitors to the Paul’s area, Marston prompts his audiences to reconceptualize one of London’s most important sites through scrutiny of its multi-layered smellscape. In the process, he develops an olfactory profile for the new Paul’s that associates his theatre with refined luxury, fashion, and sometimes risqué sensuality.